DAYA TARIK PONPES YANMU NW PRAYA SEBAGAI PILIHAN MASYARAKAT DALAM PENDIDIKAN ANAK DI KABUPATEN LOMBOK TENGAH - Hariawan, Rudi (Jurnal Paedagogy, 2020)
This study aims to describe the attractiveness of Islamic boarding schools as the primary choice of the people of Central Lombok in child education, which is focused on the management of the Islamic Boarding Schools and the reasons people choose the Ponpes. The research method used a qualitative approach with a case study design, while the data analysis used interactive methods from Miles & Huberman. From the results and discussion of the research, it can be concluded that (1) The attractiveness of Islamic boarding schools is due, first, to the superior programs of Islamic boarding schools in the fields of Islamic religious education and general education; second, skilled students in foreign languages (Arabic-English); third, the availability of adequate and modern enough facilities and infrastructure, (2) the reason the community chose the Yanmu NW Praya Islamic boarding school was because; first, the cutting down of mutually beneficial social and religious relations between Ponpes and stakeholders or the community; second, the boarding school conveys and displays the achievements of the santriwan / wati to the community as a form of responsibility to the community, especially the guardians of students in various activities, both outside and inside the Ponpes.